Effect of Ethanol On The Combustion Characteristic Of Palm Biodiesel - Chee, Kong Meng (2020)
The use of diesel fuel has contributed to the environmental degradation due to its harmful emission. Particularly, the main pollutants emitted from the burning of diesel fuel include particulate matter (PM), carbon monoxide (CO), nitrogen oxide (NOx) and unburnt hydrocarbons (UHC). In addition, the increasing global demand for diesel fuel has caused the depletion crisis of the fossil fuels. Therefore, there is a need in searching of an alternative fuel for diesel engines. Biodiesel-ethanol blends may be a solution to the aforementioned issues. The present study aims to investigate the effect of ethanol on the combustion characteristics of palm biodiesel. In which palm biodiesel and its blend with ethanol at 10 %, 20 % and 30 % blending ratios are the fuels under investigation. Single droplet combustion experiment was adopted to study the combustion characteristics of the test fuels, through a time-based image capturing method. Thereafter, the images of the combustion process were then going through image processing using MATLAB to obtain the temporal variation of droplet area and diameter during combustion. Finally, classical D2 law was used for the computation of burn rate constant for the test fuels. In regard to the experimental results, BE blends (palm biodiesel-ethanol blended fuel) have shown an adverse effect on the ignition delay. The prolonged ignition delay is likely attributed to the higher latent heat of vaporization and lower cetane number of the ethanol. Yet, BE blends have shown improved performance on the burning rate and combustion duration, with a maximum improvement of 23.15 % (increased burn rate constant) and 16.39 % (reduced combustion duration) respectively at 30 % ethanol composition, owing to their high oxygenated content that promotes a cleaner and more complete burning process. While these are not the only gains, it is found that the micro-explosion events occurred more intensively with increasing ethanol content, resulting to an enhanced evaporation rate of fuel and improved air-fuel mixing process.